Pausas e constituintes prosódicos na interpretação de atores - Fraga, Milena [UNESP] (2014)
Introduction: In speech therapy literature the work with actors, mainly treats of organic issues involved in vocal process as misuse or vocal abuse. To a lesser extent, it is possible to find works from this same literature that address issues about acting and expressive resources, besides a few of them highlighting the importance of linguistic resources in acting. Concerning the Linguistics literature, pause is dealed from the concepts of phonetics and phonology on several language levels. In this study, we propose to observe how a linguistic resource – the pause – works in theatrical acting. Bounded by the Speech Therapy field, we seek to theoretical facts from the field of Linguistics, but essentially from Prosodic Phonology. Particularly, we point out prosodic constituents: intonational phrase (I) and phonological utterance (U). Purpose: 1) Detection of the points of pause occurred in performing the same text by ten actors. 2) Data collection of the physics characteristics of pauses length. 3) Verification on how pauses length relates with where it has occurred itself, considering prosodic boundaries of intonational phrase (I) and phonological utterance (U). Methods: We have recorded a voice narration of ten different actors, which individually, performed the same single piece of text. After record transcription, a group of ten judges individually identified the points they considered to occur pauses. Only positions holding at least 70% of the votes were acceptable for use in this research. For measures of length, in seconds, it’s been defined those VVs units occurring pauses. To analyze the statistics, it’s been calculated VV’s units measures of central tendency and dispersion, in Is and Us limitations. Significance level adopted: 0,05. Results: Mean duration for I limitations was 0,77 and 1,04 for U limitations. Standard deviation for I limitations was 0,27 and 0,30...